1994
DOI: 10.1111/j.1365-2265.1994.tb03927.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cardiolipin antibodies in autoimmune thyroid diseases

Abstract: Summary OBJECTIVE In recent years anti‐phospholipid antibodies have gained much attention since they are frequently associated with thrombosis, recurrent abortion, and thrombocytopenia. Besides disease‐specific autoantibodies, other autoantibodies reactive with both organ and non‐organ specific autoantigens have been found in patients with autoimmune thyroid diseases. Therefore the objective of this study was to evaluate the presence and significance of anti‐phospholipid antibodies in untreated patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 14 publications
0
25
1
Order By: Relevance
“…Paggi et al found antiphospholipid antibodies in 17 of 31 patients (55%) with autoimmune thyroid diseases. The antibody titer was highest in patients with Graves' disease and decreased with methimazole treatment [47]. Likewise, Marongiu et al [52] found an increased incidence of antiphospholipid antibody positivity in Graves' disease patients compared to healthy controls (38% vs. 0%).…”
Section: Antiphospholipid Syndrome and Autoimmune Thyroid Disordersmentioning
confidence: 96%
See 1 more Smart Citation
“…Paggi et al found antiphospholipid antibodies in 17 of 31 patients (55%) with autoimmune thyroid diseases. The antibody titer was highest in patients with Graves' disease and decreased with methimazole treatment [47]. Likewise, Marongiu et al [52] found an increased incidence of antiphospholipid antibody positivity in Graves' disease patients compared to healthy controls (38% vs. 0%).…”
Section: Antiphospholipid Syndrome and Autoimmune Thyroid Disordersmentioning
confidence: 96%
“…A number of case reports and small case series have documented the close link between antiphospholipid antibodies and autoimmune thyroid disorders [47][48][49][50][51][52][53][54][55]. A crossreactivity between b 2 -GPI and epitopes of thyrotropin receptor has been hypothesized as a pathogenic mechanism explaining the association between these two autoimmune conditions [56].…”
Section: Antiphospholipid Syndrome and Autoimmune Thyroid Disordersmentioning
confidence: 98%
“…For example, it is known that there is a biological link between antiphospholipid antibodies and Graves' disease (49)(50)(51)(52)(53). Moreover, Homoncik et al found increased plasma VWF levels and enhanced platelet function (as measured with PFA-100 analyzer) in patients with hyperthyroidism compared with euthyroid controls (54).…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…Dopamine receptor sensitivity is indeed increased in experimental thyrotoxic chorea [8]. The anticardiolipin antibodies, which in our patient with autoimmune thyroiditis probably were immunological epiphenomena [9], may yet have had a facilitating effect. Also, the history of vocal tics during childhood may point towards a genetic predisposition for involuntary movements.…”
Section: Discussionmentioning
confidence: 91%